Semi-interpenetrating network hydrogels based on poly(methacrylic acid) and natural polymers gelatin, chitosan, and alginate, for potential biomedical applications - Vukasin Ugrinovic; Andjela Radisavljevic; Maja Markovic; Vesna Panic; Djordje Veljovic (Macedonian Journal of Chemistry and Chemical Engineering)
Hydrogels, known for their high hydration, porosity, and permeability, are widely studied for biomedical applications. This paper reports on semi-interpenetrating network (IPN) hydrogels composed of poly(methacrylic acid) (PMA) and natural polymers (gelatin, alginate, and chitosan), synthesized via thermally-induced free-radical polymerization. The resulting hydrogels were evaluated for their physicochemical, mechanical, and drug release properties. Characterization techniques, including Fourier transform infrared (FTIR) spectroscopy, Field emission scanning electron microscope (FE-SEM), and swelling capacity analysis, demonstrated effective integration of natural polymers within the PMA network and their impact on hydrogel performance. PMA's pH sensitivity, combined with natural polymers, supports its suitability for controlled drug delivery and tissue engineering. Mechanical testing showed that adding 40 wt% of gelatin significantly increased the compressive strength from 0.16 MPa in pristine PMA to 2.35 MPa for PMA/gelatin IPN hydrogel and increased the modulus from 0.006 to 0.027 MPa. Chitosan provided moderate mechanical improvements, while alginate showed limited effects at higher concentrations. Swelling analysis revealed that the addition of gelatin and alginate reduced the equilibrium swelling ratio (ESR), suggesting denser crosslinking within the hydrogel matrix. Due to its pH-sensitive properties, chitosan had increased ESR at lower pH levels, showing potential for enhanced drug release modulation. Ciprofloxacin release studies demonstrated ESR-dependent drug release kinetics. These findings suggest that the incorporation of natural polymers, particularly gelatin, optimizes mechanical properties, pH-responsive swelling, and biocompatibility, making these hydrogels promising candidates for controlled drug delivery and tissue engineering applications.